The Impact of Volatile Anesthetic Choice on Postoperative Outcomes of Cardiac Surgery: A Meta-Analysis. (29th August 2017) - Zorrilla-Vaca, Andres; Núñez-Patiño, Rafael A.; Torres, Valentina; Salazar-Gomez, Yudy
Abstract : Objectives . To evaluate the impact of volatile anesthetic choice on clinically relevant outcomes of patients undergoing cardiac surgery. Methods . Major databases were systematically searched for randomized controlled trials (RCTs) comparing volatile anesthetics (isoflurane versus sevoflurane) in cardiac surgery. Study-level characteristics, intraoperative events, and postoperative outcomes were extracted from the articles. Results . Sixteen RCTs involving 961 patients were included in this meta-analysis. There were no significant differences between both anesthetics in terms of intensive care unit length of stay (SMD −0.07, 95% CI −0.38 to 0.24, P = 0.66 ), hospital length of stay (SMD 0.06, 95% CI −0.33 to 0.45, P = 0.76 ), time to extubation (SMD 0.29, 95% CI −0.08 to 0.65, P = 0.12 ), S100β (at the end of surgery: SMD 0.08, 95% CI −0.33 to 0.49, P = 0.71 ; 24 hours after surgery: SMD 0.21, 95% CI −0.23 to 0.65, P = 0.34 ), or troponin (at the end of surgery: SMD −1.13, 95% CI −2.39 to 0.13, P = 0.08 ; 24 hours after surgery: SMD 0.74, 95% CI −0.15 to 1.62, P = 0.10 ). CK-MB was shown to be significantly increased when using isoflurane instead of sevoflurane (SMD 2.16, 95% CI 0.57 to 3.74, P = 0.008 ). Conclusions . The volatile anesthetic choice has no significant impact on postoperative outcomes of patients undergoing cardiac surgery.